2005
DOI: 10.1002/maco.200503863
|View full text |Cite
|
Sign up to set email alerts
|

Effect of (R+, X) salts addition on nickel corrosion in 1M sulfuric acid medium

Abstract: on the corrosion behaviour of nickel when submitted to 1M sulphuric acid medium. After one hour of immersion time, we noted an acceleration of nickel corrosion process after the addition of K þ ,Cl À and K þ ,Br À in the 1M H 2 SO 4 electrolyte. K þ ,I À exhibited an inhibition of the anodic Ni corrosion process whereas the phosphonium iodine (R þ ,I À ) acts simultaneously on both processes: it is a mixed inhibitor. Such result is due to the adsorption of the alkyl group C 8 H 17 which limited oxygen diffusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…All the Nyquist plots were analysed by fi tting the experimental data to an equivalent circuit model. The model chosen for the fi tting was a commonly used model for Nickel [4] (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the Nyquist plots were analysed by fi tting the experimental data to an equivalent circuit model. The model chosen for the fi tting was a commonly used model for Nickel [4] (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…Gilli et al [2], consider that the formation of a passive fi lm on nickel surface to be the main reason for the good corrosion resistance of nickel. There are different methods to protect nickel against corrosion in acidic media such as using inhibitors and surface modifi cation [4]. Typically, the general and localized corrosion behaviour of alloys depends on their roughness and passivation behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…34 The results achieved showed that phosphonium iodide addition modies the interface behaviour due to the interaction between the molecule and the material surface. Tetrahydroxymethyl phosphonium sulfate is a wellknown phosphonium salt that shows biocidal properties against sulfate-reducing bacteria (SRB), which produce sulfuric acid in oil industry.…”
Section: -19mentioning
confidence: 91%
“…The corrosion inhibition of triphenyl phosphonium salts on various metals (Ni, Zn and Fe) and alloys in acidic media was studied by Niass et al (2001), Said et al (2005Said et al ( , 2007, Troquet and Pagetti (2004), Bhrara and Singh (2007) and Khamis et al (2000). In all these studies, the phosphorus atom and the phenyl rings in the compounds were shown to be able to adsorb very well on the metal surface and form a protective layer, which in turn increases the effectiveness of corrosion inhibition with the increase in the concentration of the inhibitor, reaching in some cases 98 and 99 per cent inhibition (Nahlé and Walsh, 1995;Bhrara and Singh, 2007), respectively.…”
Section: Introductionmentioning
confidence: 99%